POLICY CONSTRUCTION OF ISLAMIC EDUCATION AND TECHNOLOGICAL CHANGES IN THE DIGITAL ERA: THE SALAFIYAH CURRICULUM - Chaniago, Fransisko; Fitriani, Suci; Sakunti, Sri Ramdayeni; Fadlilah, Fadlilah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Research on the policy construction and implementation of the Salafiyah Curriculum in Islamic boarding schools is essential for understanding how Islamic educational institutions adapt to modern demands while maintaining traditional values. A qualitative approach was employed using participant observation, in-depth interviews, and documentation. Data were analyzed through three stages, data reduction, data presentation, and conclusion drawing. The results show that the policy construction for implementing the Salafiyah Curriculum at Sa’adatuddarein is based on the Regulation of the Minister of Religious Affairs Number 18 of 2014 Article 1 Paragraphs 1 and 4. This policy supports the school’s vision and mission to develop students who possess strong religious knowledge while remaining adaptive to social and technological changes in the globalization era. The curriculum is implemented by integrating the Salafiyah and Khalafi systems, combining the formal education curriculum with the traditional Islamic boarding school curriculum. This integration forms a holistic educational model where academic and religious activities are interconnected. The study confirms that the integration of curriculum and leadership policies at Sa'adatuddarein represents a strategic adaptation to globalization without neglecting Islamic educational values. The implications suggest that Islamic boarding schools can enhance their relevance and competitiveness by developing policies and curriculum models that balance tradition and modernity. These findings may serve as a reference for other Islamic educational institutions in designing contextual, sustainable, and quality-oriented learning systems in the global era.